New Synthetic Pyrazine Carboxamide Derivatives as Potential Elicitors in Production of Secondary Metabolite in In vitro Cultures - Tůmová, Lenka; Tůma, Jiří; Doležal, Martin; Dučaiová, Zuzana; Kubeš, Jan (Pharmacognosy magazine, 2016)
BACKGROUND: Silymarin, an active polyphenolic fraction of Silybum marianum, and high flavonoid content of Fagopyrum possess various interesting biological activities. The substituted pyrazine-2-carboxamides were previously used as effective elicitors of studied secondary metabolites. OBJECTIVE: To study the effect of new synthetic pyrazine carboxamide derivatives, N-(4-chlorobenzyl)-5-tert-butylpyrazine-2-carboxamide (1) and 3-(3-((trifluoromethyl) benzyl) amino) pyrazine-2-carboxamide (2), on flavonolignan and flavonoid production in S. marianum and Fagopyrumes culentum in vitro cultures. MATERIALS AND METHODS: Callus and suspension cultures were cultured on MS medium containing α-naphtaleneacetic acid or 2,4-D. Three elicitor concentrations for different exposure times were tested. Dried and powdered samples of callus and suspension cultures were extracted with methanol and analyzed by DAD-HPLC. RESULTS: Compound 1 showed as a good elicitor of taxifolin production. The effect on silymarin complex was less visible with a maximum between 24 and 48 h after 3.292 ×10(-4) mol/L concentration. The detailed analysis showed that silychristin was the most abundant. Compound 2 was effective in rutin production only in callus culture with maximum 24 h and 168 h after application of 3.3756 ×10(-3) mol/L concentration and 48 and 72 h after 3.3756 ×10(-4) mol/L concentration. CONCLUSION: From the results of the performed experiments, it can be concluded that compound 1 shows to be suitable elicitor for enhanced production of taxifolin and silychristin in S. marianum, mainly when 3.292 ×10(-4) mol/L concentration was used, and compound 2 is suitable for increase rutin production in callus cultures and less appropriate for suspension cultures of F. esculentum. SUMMARY: The influence of two new synthetic pyrazine-2-carboxamidesderivatives on secondary metabolite content of Silybum marianum and Fagopyrum esculentum in vitro cultures was tested.In S. marianum, the derivate N-(4-chlorobenzyl)-5-tert-butylpyrazine-2-carboxamide showed as a good elicitor of taxifolin production and less effective for silymarin complex production with silychristin as the most abundant.The derivate 3-(3-((trifluoromethyl) benzyl) amino) pyrazine-2-carboxamide is suitable for increase rutin production in callus cultures and less appropriate for suspension cultures of F. esculentum.
Keywords: pyrazine carboxamide; flavonolignans; Fagopyrum; flavonoids; Silybum